Enterprises’ Heterogeneous Preferences for Incentive Policies of Poverty Alleviation in China - Wei Liu; Xiyan Han; Guiqin Zhou (SAGE Open)
Enterprises, including small and medium-sized enterprises (SMEs), can cause poverty alleviation. (1) Background: Evaluating the incentive policies favored by Chinese enterprises could aid policymakers in formulating more efficient and targeted policy measures. (2) Methods: This study uses Choice Experiments to examine policy preferences. The data was analyzed using the Conditional Logit and Mixed Logit models. (3) Results: The findings indicate a significant preference among enterprises for financial policies and production factor policies. Private enterprises exhibit a higher preference for the financing interest rate policy. Moreover, the longer a firm has been established, the stronger its preference for the financing interest rate policy becomes. Moreover, high-tech enterprises show a greater inclination towards the preferential land policy. (4) Conclusions and policy recommendations: Enterprises exhibit a policy preference effect, and policy preferences exhibit heterogeneity. To enhance policy efficiency, the government should formulate policies that cater to the diverse preferences of enterprises. Specifically, enterprises with longer establishment years and private enterprises could be offered preferential financing policies, such as favorable interest rates or financial subsidies, as incentives to encourage their active involvement in poverty alleviation efforts. Findings from this research will enable policy makers to make more informed decisions about future policy proposals taking into account enterprises preferences for the policies of participating in poverty alleviation.